The OAS guide on the law applicable to international investment arbitration - Moreno Rodríguez, José Antonio (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This article provides insights into the new OAS Guide on the Law Applicable to International Investment Arbitration, a crucial instrument that grapples with the intricacy of the issue from a cross-disciplinary perspective. The Guide is a product of the urgent necessity to bring clarity to this field of practice. It not only highlights the significance of the topic but also delves into its origins, sources, structure, and current developments, all with the aim of fostering a more profound understanding and empowering a consistent application of the applicable substantive law in international investment arbitration.